2017
DOI: 10.1016/j.pbb.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response characteristics of intravenous ketamine on dissociative stereotypy, locomotion, sensorimotor gating, and nociception in male Sprague-Dawley rats

Abstract: Clinicians administer subanesthetic intravenous (IV) ketamine infusions for treatment of refractory depression, chronic pain, and post-traumatic stress disorder in humans. However, ketamine is administered via the subcutaneous (SC) or intraperitoneal (IP) routes to rodents in most pre-clinical research, which may limit translational application. The present study characterized the dose-response of a subanesthetic IV ketamine bolus (2 and 5mg/kg) and 1-h infusion (5, 10, and 20mg/kg/h) on dissociative stereotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 64 publications
(90 reference statements)
4
29
0
1
Order By: Relevance
“…Furthermore, the results of IV administration depend on whether the drug is administered through a rapid bolus (one-time IV injection) or a prolonged infusion with a mechanical syringe pump. Consistent with these observations, a preclinical study observed that a ketamine bolus (2 and 5 mg/kg, IV) produced rapid and robust dissociative stereotypy [ 24 ], while a ketamine infusion (10 mg/kg, IV) over 2 h produced hypo-locomotor activity (a sign of sedation and analgesia) in rats [ 20 , 22 ]. Because the IV route is rarely used in preclinical studies, it is critical to utilize the IV ketamine administration technique to a larger extent in preclinical research in order to better model the clinically relevant route of ketamine administration.…”
Section: Effects Of Ketamine On Fear Memorymentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, the results of IV administration depend on whether the drug is administered through a rapid bolus (one-time IV injection) or a prolonged infusion with a mechanical syringe pump. Consistent with these observations, a preclinical study observed that a ketamine bolus (2 and 5 mg/kg, IV) produced rapid and robust dissociative stereotypy [ 24 ], while a ketamine infusion (10 mg/kg, IV) over 2 h produced hypo-locomotor activity (a sign of sedation and analgesia) in rats [ 20 , 22 ]. Because the IV route is rarely used in preclinical studies, it is critical to utilize the IV ketamine administration technique to a larger extent in preclinical research in order to better model the clinically relevant route of ketamine administration.…”
Section: Effects Of Ketamine On Fear Memorymentioning
confidence: 77%
“…These results highlight the importance of the route of ketamine administration (IV vs. IP) and the duration of the drug peak effects. Differences in the pharmacokinetics of IP and IV administration could potentially influence ketamine’s effect on fear memory, as an IV infusion allows the drug plasma concentration to maintain a steady state over a longer duration following a lower dose in the body, compared to an IP method that produces a rapid peak and then trough of plasma concentration [ 23 , 24 ]. Additionally, IV ketamine does not undergo first-pass metabolism because it bypasses the liver upon initial administration, leading to greater bioavailability at target organs.…”
Section: Effects Of Ketamine On Fear Memorymentioning
confidence: 99%
“…Following an IP injection in rodents, ketamine plasma levels rapidly peak and decline secondary to drug distribution and elimination 24 26 . In comparison, a continuous IV ketamine infusion maintains consistent elevated plasma drug levels over an extended period of time 27 , which allows for sustained impact on neurobiological mechanisms in the brain. To our knowledge, there are no previous reports of the effects of IV ketamine infusion on fear memory retrieval, extinction, and recall in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy and precision of our method was generally better than those of previous ones. In the previous publications, the accuracy and precision were 5–11% and 2.5–8.1%, respectively (Cirimele, Villain, Pépin, Ludes, & Kintz, ; Giroux, Santamaria, Hélie, & Burns, ; Knibbe et al, ; Li et al, ; Lian et al, ; Probst, Blobner, Luppa, & Neumeier, ; Radford et al, ; Seno, He, Tashiro, Ueyama, & Mashimo, ; Seplúveda et al, ; Thieme, Sachs, Schelling, & Hornuss, ; Veilleux‐Lemieux, Beaudry, Hélie, & Vachon, ).…”
Section: Resultsmentioning
confidence: 92%